Angling sport fishing in Lobo-Broa reservoir (Itirapina, SP, Brazil) - Pereira,JMA. (2008)
The objective of this paper was to study angling from September, 2002 to September, 2004 in the Lobo-Broa Reservoir, Itirapina, SP (22° 15' S and 47° 49' W). Interviews (total 1,027) with sport fishers were accomplished in the three main fishing sites (Horto, Píer and Praia). This fishing was practiced with a simple fishing rod and reel, mainly in Horto, where the catches and fishing effort were higher. The catches were mainly composed of Cichlidae (Geophagus brasiliensis, Oreochromis niloticus, Tilapia rendalli and Cichla monoculus). We tried to determine which factors (fishing sites, type of baits and season) and the covariate fishing effort, expressed in number of fishing rods multiplied by fishing time, would affect catches, using a 3 way-ANCOVA. The final model showed that only fishing sites and effort determined the captures of sporting fishing in the reservoir. Some measures for managing fishing practices are discussed.